Critical success factors of Accounting Information Systems (AIS): empirical evidence from Malaysian organizations / Sharina Tajul Urus … [et al.] - Tajul Urus, Sharina; Hasim, Khuziah; Syed Mustapha Nazri, Sharifah Nazatul Faiza; Tuan Mat, Tuan Zainun (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2020)
The role of Information System (IS) has changed and progressed rigorously over the last decade because of its ability to speed up the decision-making process. Effective and efficient management of an organization is usually reflected through the quality of decision made through financial systems like Accounting Information Systems (AIS). AIS is often viewed as medium to enhance the capability and efficiency of business operations. However, previous studies have suggested that the success of AIS often relies on critical success factors. This study aims to examine the critical success factors on the net benefits of AIS. The purpose of this paper is to determine the influence of system quality, service quality, system use and user satisfaction and the interaction of these factors on the AIS net benefits. Based upon the lens of DeLone and McLean’s Information System Success Model (2003), this study adopted a quantitative method through an online survey of 150 AIS users at various Malaysian organizations. Data was analysed by using the multiple regression method. The result suggests that system quality and service quality influence system use and user satisfaction which also affect net benefits of AIS. This study extends the existing IS literature especially in identifying the critical success factors on net benefits of AIS. Ultimately, the use of the critical success factors of AIS can raise the level of users’ belief in it. From the practitioners’ perspective, this study can be useful for organizations when selecting and implementing a system.